2018
DOI: 10.1186/s12939-018-0816-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of underweight among children 6–59 months of age in Takusa district, Northwest Ethiopia

Abstract: BackgroundMost of the nearly 104 million underweight children in the world lived in South East Asia and sub-Saharan Africa in 2010. According to the 2014 Ethiopian Demographic and Health Survey (EDHS) report, 24 and 7% of children aged 6–59 months were underweight and severely underweight, respectively. Although appropriate child feeding and nutritional interventions reduce child illness and death, malnutrition remains a leading public health problem in Ethiopia. As literature on the issue is scarce in northwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
29
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 30 publications
13
29
9
1
Order By: Relevance
“…Children from rural areas were 1.16 times more likely to be underweight compared to children from urban areas. This nding is in agreement with the study conducted in Takusa district, Northwest Ethiopia [16]. The remarkable difference in the rate of underweight among rural and urban children might be differences in living circumstances, deviations in early screening of mothers at child conception in urban areas compared with rural areas, exposure to poor dietary diversity and greater risks of infections among rural children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Children from rural areas were 1.16 times more likely to be underweight compared to children from urban areas. This nding is in agreement with the study conducted in Takusa district, Northwest Ethiopia [16]. The remarkable difference in the rate of underweight among rural and urban children might be differences in living circumstances, deviations in early screening of mothers at child conception in urban areas compared with rural areas, exposure to poor dietary diversity and greater risks of infections among rural children.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of stunting, underweight and wasting in Amhara region was 46.3%, 28.4% and 9.8%, respectively. In this study, stunting and underweight are higher than that of the studies conducted in Ethiopia which were 38.3% and 23.3% [8], in Dale district 25.6% and 19% [15], Takusa district 36.5% and 19.5% [16], respectively. The prevalence of stunting and underweight in this study is higher than the nding reported in Nairobi Peri-Urban Slum 30.2% and 14.9% [17], respectively.…”
Section: Discussioncontrasting
confidence: 70%
“…Children from rural areas were 1.16 times more likely to be underweight compared to children from urban areas. This nding is in agreement with the study conducted in Takusa district, Northwest Ethiopia [15]. The remarkable difference in the rate of underweight among rural and urban children might be differences in living circumstances, deviations in early screening of mothers at child conception in urban areas compared with rural areas, exposure to poor dietary diversity and greater risks of infections among rural children.…”
Section: Discussionsupporting
confidence: 91%
“…and 19% [14], Takusa district 36.5% and 19.5% [15], respectively. The prevalence of stunting and underweight in this study are higher than the nding reported in Nairobi Peri-Urban Slum 30.2% and 14.9% [16], respectively.…”
Section: Discussionmentioning
confidence: 94%
“…It kills 3.1 million under-ve children every year [1][2]. Under-ve children are the most susceptible age group for malnutrition [3]. Malnutrition at the early stages of life can increase risk infections, morbidity, and mortality, together with decreased mental and cognitive development.…”
Section: Introductionmentioning
confidence: 99%